Using iPSC‐derived human DA neurons from opioid‐dependent subjects to study dopamine dynamics. Issue 8 (25th May 2016) - Sheng, Yang; Filichia, Emily; Shick, Elizabeth; Preston, Kenzie L.; Phillips, Karran A.; Cooperman, Leslie; Lin, Zhicheng; Tesar, Paul; Hoffer, Barry; Luo, Yu
Abstract: Introduction: The dopaminergic (DA) system plays important roles in addiction. However, human DA neurons from drug‐dependent subjects were not available for study until recent development in inducible pluripotent stem cells (iPSCs) technology. Methods: In this study, we produced DA neurons differentiated using iPSCs derived from opioid‐dependent and control subjects carrying different 3′ VNTR (variable number tandem repeat) polymorphism in the human dopamine transporter ( DAT or SLC6A3 ). In addition, the effects of valproic acid (VPA) exposures on iPSC‐derived human DA neurons are also examined. Results: We present the first evidence suggesting that the 3′ VNTR polymorphism in the hDAT gene affects DAT expression level in iPSC‐derived human DA neurons. In human DA neurons, which provide an appropriate cellular milieu, VPA treatment alters the expression of several genes important for dopaminergic neuron function including DAT, Nurr1, and TH; this might partly explain its action in regulating addictive behaviors. VPA treatment also significantly increased DA D2 receptor ( Drd2 ) expression, especially in the opioid‐dependent iPSC cell lines. Conclusions: Our data suggest that human iPSC‐derived DA neurons may be useful in in vitro experimental model to examine the effects of genetic variation in gene regulation, to examine the underlying mechanisms in neurological disorders including drug addiction, and to serve as a platform for therapeutic development. Abstract : Using iPSC technology, we produced dopaminergic neurons differentiated using iPSCs derived from opioid‐dependant and control subjects. In this study, we present the first evidence suggesting that the 3′ VNTR polymorphism in human dopamine transporter ( DAT or SLC6A3 ) gene affects human DAT expression level in iPSC‐derived human dopaminergic neurons. In addition, the effects of valproic acid exposures on iPSC‐derived human DA neurons are also examined.